The incorporation of comorbidities in the prognostication of patients with lower-risk myelodysplastic syndrome*. Issue 8 (3rd August 2017) - Falantes, Jose F.; Márquez-Malaver, Francisco J.; Knight, Teresa; Calderón-Cabrera, Cristina; Martino, María L.; González, Jose; Montero, Isabel; Espigado, Ildefonso; Pérez-Simón, Jose A.
Abstract: Chronic medical diseases, evaluated by several comorbidities indexes have been reported to influence on overall survival in patients with myelodysplastic syndrome (MDS). However, these studies included patients with lower and higher-risk disease by IPSS. This study retrospectively evaluates the role of comorbidities (evaluated by the MDS comorbidity index; MDS-CI) together with clinical parameters in a series of 232 patients with LR-MDS (defined as either an IPSS score of low/intermediate-1 and favorable cytogenetic categories by IPSS-R). In multivariate analysis, together with age >75 years, diabetes requiring therapy and hemoglobin <10 g/dL; the incorporation of comorbidities by the MDS-CI (HR = 2.5; p < 0.0001) were independently associated to the probability of nonleukemic death (NLD). The combination of these variables allowed development of a model, which categorizes patients in three different groups with significantly different probability of NLD overtime ( p < 0.001). This integrated score confirms the importance of comorbidities at diagnosis of patients with LR-MDS.